FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENGETAHUAN REMAJA TENTANG KESEHATAN REPRODUKSI DI SMU GEMA BUANA BANDAR KHALIPAH - Purba, Agnes; Rahayu, Reny (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
The main problem of adolescent reproductive health (KRR) in Indonesia, is the lack of information on reproductive health, the problem of shifting adolescent sexual behavior, poor health services and unsupportive legislation. The problem of adolescents in the Bandar Khalifah Health Center Work Area is that there are 103 teenagers who dropped out of school because of early marriage. The purpose of this study was to analyze factors related to adolescent knowledge about reproductive health at Gema Buana High School, with a correlation analytic research design.The population and sample were 72 high school students. The results showed that there was a relationship between the role of parents (p = 0.012), the role of peers (p = 0.000) and sources of information (0.030) with adolescent knowledge about reproductive health. For this reason, it is suggested to Gema Buana High School to establish PIK-KR as a means for students to gather information about reproductive health.